Annonaceous Acetogenins with insecticidal effects on Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) - Ruiz Hidalgo, José (2018)
Background: Annonaceous acetogenins enclose a large number of biological activities, among which the insecticidal stands out. Methods: We report herein the biocide effects of natural acetogenins from Annona squamosa, A. muricata and A. montana seeds: annonacin, cis-annonacin, cis-annonacin-10- one, asimicin, rolliniastatin-2, cherimolin-1, cherimolin-2, almuñequin, and two β-OH acetogenins: laherradurin and itrabin on Spodoptera frugiperda Smith (Lepidoptera: Noctuidae). Also, some acetylated and methoxy methylated ACG derivatives were synthesized and evaluated: annonacin (3 OAc), annonacin (4 OAc), asimicin (3 OAc), rolliniastatin-2 (3 OAc), rolliniastatin-2 (MOM), laherradurin (3 OAc) and itrabin (3 OAc). Results: The natural acetogenin rolliniastatin-2 (100 μg·g-1 of diet) produced the most important toxic action causing 100% mortality of early instar larvae. Derivatization of ACG yielded compounds that produced nutritional alterations. The incorporation of rolliniastatin-2 (3 OAc) and rolliniastatin-2 (3 MOM) (100 μg·g-1) into the artificial diet of Spodoptera frugiperdadisplayed the strongest antifeedant effects causing marked decreasings in larval growth and adult lethal malformations. Conclusion: Natural acetogenins are promising metabolites for insect control. Derivatization of these compounds reduces their toxicity to early instar larvae.